Modern Surface Engineering Treatments - Aliofkhazraei, Mahmood (IntechOpen, 2013)
Surface engineering can be defined as an enabling technology used in a wide range of industrial activities. Surface engineering was founded by detecting surface features which destroy most of pieces, e.g. abrasion, corrosion, fatigue, and disruption; then it was recognized, more than ever, that most technological advancements are constrained with surface requirements. In a wide range of industry (such as gas and oil exploitation, mining, and manufacturing), the surfaces generate an important problem in technological advancement. Passing time shows us new interesting methods in surface engineering. These methods usually apply to enhance the surface properties, e.g. wear rate, fatigue, abrasion, and corrosion resistance. This book collects some of new methods in surface engineering.